Parental bonding may moderate the relationship between parent physical activity and youth physical activity after school - Dzewaltowski, David A.; Ryan, Gregory J.; Rosenkranz, Richard R. (My University, 2011)
Objectives: The processes and conditions through which parents may influence children's physical activity have not been identified. This study tested the hypothesis that bonding with parents would moderate the relationships between parental physical activity and youth physical activity. Design: A cross-sectional preliminary study. Methods: A total of 57 sixth and seventh grade students completed a survey that assessed bonding with parents and parental physical activity. Then, on 3 days, they reported their moderate and vigorous physical activity using the Previous Day Physical Activity Recall. Results: Hierarchical multiple regression analyses showed a moderation effect such that the interaction between bonding with parents and parental physical activity significantly predicted youth physical activity after controlling for their main effects. Conclusion: This preliminary study suggests that interventions targeting parents as the route to increasing physical activity may need to target both increasing parental physical activity and the parent--child bond.
Keywords: Children; Mediator; Social development model